Third Hand : Collaboration in Art from Conceptualism to Postmodernism - Green, Charles, 1953- (Book collections on Project MUSE., 2001)
Since the 1960s, a number of artists have challenged the dominant paradigm of art-that of the lone artist-by embarking on long-term collaborations that dramatically altered the terms of artistic identity. In The Third Hand, Charles Green offers a sustained critical examination of collaboration in international contemporary art.